Latin American &Amp; Caribbean Petroleum Engineering Conference 2007
DOI: 10.2118/107899-ms
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis for PCP Systems

Abstract: One of the concerns that artificial lift engineers have to face when they are working with PCP systems is the lack of information about effective procedures for PCP diagnosis and optimization. Most of the information available is limited to explaining the importance of keeping the fluid level over the pump to avoid dry run. On the opposite side, there are some studies that explain the hydrodynamics of the pumps, and how some variables, like intake void fraction and fluid viscosity affect the pump performance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The rotor is made of steel to resist various corrosion factors, while the stator is made in the form of a helical screw. The joint work of these two elements forms a progressive cavity pump by forming cavities between the stator and the moving part (rotor) [24] where these cavities are filled with fluid when the pump rotates and rises to the top of the well as a result of the pressure provided by the pump [23]. The pump depends in its work when transferring fluids from the bottom to the surface on achieving an ideal intersection between the rotor and the stator and avoiding the fluids slipping by maintaining the clearance between the rotor and the stator properly closed so pumps using elastomers to remain the dominant due to their economic advantage, ability to handle abrasive fluids, and low slippage [25], where cavities are formed separated from each other when rotating [26][27]…”
Section: Progressive Cavity Pumpmentioning
confidence: 99%
“…The rotor is made of steel to resist various corrosion factors, while the stator is made in the form of a helical screw. The joint work of these two elements forms a progressive cavity pump by forming cavities between the stator and the moving part (rotor) [24] where these cavities are filled with fluid when the pump rotates and rises to the top of the well as a result of the pressure provided by the pump [23]. The pump depends in its work when transferring fluids from the bottom to the surface on achieving an ideal intersection between the rotor and the stator and avoiding the fluids slipping by maintaining the clearance between the rotor and the stator properly closed so pumps using elastomers to remain the dominant due to their economic advantage, ability to handle abrasive fluids, and low slippage [25], where cavities are formed separated from each other when rotating [26][27]…”
Section: Progressive Cavity Pumpmentioning
confidence: 99%
“…When gas is present in the flow stream, as the volume displaced is constant (but the density increases with pressure), the pressure distribution along the pump becomes nonlinear, and the slippage between cavities is not constant along the pump. Experimental tests showed that disproportional pressure distribution causes premature failure of pump's components, which limits the pumping of high GVFs flows (Bratu 2005). In these cases, for a constantvolume displaced pump, the liquid return is, at least, equal to the volume reduction of the gas.…”
Section: Pcp Dynamicsmentioning
confidence: 99%